A Qualitative Comparison of Reassurance Approaches Used by Physical Therapists to Address Fears and Concerns of Patients With Nonspecific Neck Pain and Whiplash-Associated Disorders: An Online Survey. Issue 7 (13th April 2020) - Silva Guerrero, Alma Viviana; Setchell, Jenny; Maujean, Annicke; Sterling, Michele
Abstract: Objectives: The study aimed to identify and compare (1) what physical therapists perceive to be the main concerns, fears, and worries that patients with whiplash-associated disorders (WAD) and nontraumatic neck pain (NTNP) have as a result of their condition, and (2) the strategies used by physical therapists to address these fears and concerns. Methods: Using convenience sampling, 30 physical therapists completed 2 online open-ended surveys. The responses were analyzed using 2 descriptive analytic methods (thematic analysis and constant comparative analysis), and then themes were examined for areas of convergence and divergence. Results: Four similar themes for both neck pain groups were produced from our analysis of the survey responses: (1) interference with daily life, (2) concerns related to pain, (3) psychological distress, and (4) ``When I will recover?'' Subthemes differed between the groups. For example, the theme "psychological distress" had subthemes of anger and thoughts about no resolution for the WAD group, whereas for the NTNP group, subthemes were anxiety and uncertainty. The only divergent theme was (5) fear avoidance, present in the NTNP group only. Analysis of physical therapist strategies identified 3 consistent themes and 5 divergent themes across the 2 groups. Conclusions: Physical therapists described a wealth of reassurance strategies for individuals with NTNP and WAD. There were several shared themes but also some discordant ones. Reassurance is multifactorial and needs to be nuanced and not prescriptive. Impact: These qualitative findings may be key to inform the differentiated content of training programs for physical therapists delivering reassurance for these 2 populations.